Analisis Kelayakan Lokasi dan Finansial Pembangunan Industri Pengolahan Karet di Pesisir Timur Provinsi Aceh - Akhmad Baihaqi (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
Abstract. Aceh is one among 15 provinces which are centers of rubber plantations in Indonesia. Rubber plantations in Aceh divided by smallholder plantations and large estates. Until 2011, BPS recorded that communities rubber plantation area was 122.660 ha with a production of 69.972 tons per year, and a large farming area was 21.631 ha with a production of 17.435 tons per year . This study aimed to determine the location of the development of the rubber industry and calculate the cost of investment required to establish rubber industry. The data collected was obtained from field surveys and literatures in the district that has rubber production in the Eastern Region of the Aceh Province. The results of location analysis showed that East Aceh, Aceh Tamiang and South East Aceh are the three priority ranking area which feasible to set up a rubber processing industry in Aceh. Financial calculation was done for the rubber processing industry (crumb rubber) with capacity of 10,000 tons per year and assuming 20-year economic life. Results showed that: Investment Cost; IDR 36.189.274.000, Operating Costs; IDR 116.22 billion, Production and Revenue; 71.040 Tons; IDR 1.842.720.768.000, Gross Benefit; IDR 163.432.239.000 Net Benefit; Rp. 114.402.567.000, NPV; IDR 32.375.726.000, NBCR; 1,38, 21,58 percent of IRR, and Payback Period is 7 year and 6 months.